Dual-functional SPVDF / SPBI composite proton exchange membrane and preparation method thereof

By functionalizing PVDF nanofibers and filling with sulfonated polybenzimidazole, combined with the use of crosslinking agents, the problem of poor compatibility between PVDF nanofibers and polyelectrolytes is solved, and the mechanical properties and protons of the composite proton exchange membrane are improved. Conductive performance, forming a high-performance SPVDF/SPBI composite film.

CN119324239APending Publication Date: 2025-01-17HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325671.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the prior art, the compatibility between PVDF nanofibers and polyelectrolytes is poor, resulting in poor mechanical properties and proton conduction properties of the composite proton exchange membrane.

Method used

The PVDF nanofibers were subjected to one-step co-deposition treatment of polydopamine and benzyl disulfonic acid to improve their hydrophobicity, and the sulfonated polybenzimidazole was filled into the functionalized PVDF fibers with crosslinking agents added to enhance interactions and fill effect, forming a dual-functional SPVDF/SPBI composite proton exchange membrane.

Benefits of technology

The mechanical properties, oxidation stability and proton conduction properties of the composite membrane are significantly improved, forming a proton exchange membrane with high strength and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324239A_ABST
    Figure CN119324239A_ABST
Patent Text Reader

Abstract

The invention relates to a dual-functional SPVDF / SPBI composite proton exchange membrane and a preparation method thereof, and the preparation method comprises the following steps: soaking PVDF nanofibers in a buffer solution containing dopamine, then adding disulfonic acid benzidine, carrying out a one-step co-deposition reaction, and carrying out post-treatment to obtain dual-functional PVDF; and soaking the bifunctional PVDF in a sulfonated polybenzimidazole solution, adding a cross-linking agent, and drying to obtain the bifunctional SPVDF / SPBI composite proton exchange membrane. The PVDF substrate fiber is subjected to surface functionalization treatment, so that the hydrophobicity of the PVDF nanofiber can be greatly improved, the interaction force between the PVDF nanofiber and the sulfonated polybenzimidazole polymer is enhanced, and the conduction performance is improved; chemical reaction crosslinking is realized by adding a crosslinking agent; therefore, the composite proton exchange membrane with strong mechanical property, high oxidation stability and good conductivity is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of proton exchange membranes, and in particular to a dual-functional SPVDF / SPBI composite proton exchange membrane and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is a device that can directly convert chemical energy in fuel into electrical energy through electrochemical reactions. It is also considered one of the most promising clean energy conversion technologies for commercialization. Among them, the proton exchange membrane, as the core component of the fuel cell, plays an important role in conducting protons, blocking electrons, and separating the positive and negative electrodes. Its performance directly determines the performance of the fuel cell. As a polyelectrolyte membrane material, the proton exchange membrane must have (1) high proton conductivity; (2) good chemical stability and temperature stability to ensure that the battery can operate reliably at a specific temperature for a long time; (3) excellent alcohol permeation resistance, which can reduce fuel loss and reduce costs, and also avoid catalyst poisoning; (4) good mechanical properties to withstand the mechanical pressure caused by battery operation. In order to meet the above application requirements, polymer homogeneous proton exchange membranes are currently widely studied. According to the different chemical compositions of the polymers, they can be divided into fluorinated proton exchange membranes and non-fluorinated proton exchange membranes. Generally, homogeneous electrolyte membranes have high proton conductivity but often show unsatisfactory mechanical properties. Therefore, in order to obtain a proton exchange membrane with excellent comprehensive performance, strategies such as preparing polymer blended polyelectrolyte membranes, organic-inorganic composite polyelectrolyte membranes, and porous substrate reinforced composite polyelectrolyte membranes are effective ways to solve the above problems.

[0003] Among them, the preparation of porous substrate reinforced composite polyelectrolyte membrane has unique advantages. Flexible porous substrates have excellent mechanical properties, such as ductility, tensile strength, compressive strength, etc. Some common porous substrates, such as porous polytetrafluoroethylene (PTFE), porous polypropylene, porous polyvinylidene fluoride (PVDF), porous polyethylene, etc., have been increasingly widely used as mechanical reinforcement substrates for polymers. Among them, the flexible porous substrates prepared by electrospinning have attracted widespread attention from researchers. Electrospinning is a process of spinning polymers or melts into fibers through an electrostatic field. The prepared fibers have micro-nanoscale sizes, which can form a fiber network or fiber layer and finally form a porous substrate. And by controlling the diameter and layout of the fibers, the size and structure of the porous substrate pores can be adjusted. Applied in fuel cells, electrospun fibers have a high specific surface area and can provide a larger support area, greatly enhancing the overall mechanical strength of the proton exchange membrane, and the porous structure also helps to improve the transmission performance of gases and liquids, thereby improving the reaction rate of fuel cells.

[0004] Among them, PVDF electrospun nanofibers are an ideal mechanical support matrix material with high flexibility, high chemical stability and easy electrospinning. PVDF electrospun nanofibers are used as porous substrates and then filled with polyelectrolyte materials to prepare composite membranes. The introduction of PVDF can effectively improve the water absorption and swelling of polyelectrolytes and improve mechanical properties. For example, it is used in the functional modification of Nafion and chitosan composite membranes. However, pure PVDF nanofibers have strong hydrophobicity and poor compatibility with polyelectrolytes, which leads to the easy appearance of voids and defects in the polyelectrolyte filling process, which has a certain impact on the mechanical properties and electrochemical properties of the composite membrane. Therefore, how to effectively improve the interfacial interaction between PVDF nanofibers and polyelectrolytes, while improving the polyelectrolyte filling effect, giving better mechanical properties and proton conduction performance is crucial. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a bifunctional SPVDF / SPBI composite proton exchange membrane and a preparation method, and solve the technical problem in the prior art that the mechanical properties and proton conductivity of the composite proton exchange membrane are poor due to the poor compatibility between PVDF nanofibers and polyelectrolytes.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a bifunctional SPVDF / SPBI composite proton exchange membrane, comprising the following steps: (1) immersing PVDF nanofibers in a buffer solution containing dopamine, adding diphenyl sulfonate to perform a one-step co-deposition reaction, and obtaining bifunctional PVDF through post-treatment; (2) immersing the bifunctional PVDF in a sulfonated polybenzimidazole solution, adding a cross-linking agent, and obtaining a bifunctional SPVDF / SPBI composite proton exchange membrane through drying.

[0007] In a second aspect, the present invention provides a bifunctional SPVDF / SPBI composite proton exchange membrane prepared by the above preparation method.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention performs surface polydopamine (PDA) and disulfonic acid benzidine functionalization treatment on PVDF base fibers, which can not only greatly improve the hydrophobicity of PVDF nanofibers and strengthen the interaction between PVDF nanofibers and sulfonated polybenzimidazole (SPBI) polymers, but also introduce a large number of amino and sulfonic acid groups, which can not only directly improve the proton transfer rate, but also form ionic acid-base pairs by interacting with the functional groups on the SPBI main chain, thereby constructing an effective hydrophilic channel to promote proton transfer and improve the conductivity performance; by adding a cross-linking agent to achieve chemical reaction cross-linking, the interaction with SPBI is effectively improved, a better filling effect is achieved, and a wide range of proton transfer channels are constructed, thereby preparing a composite proton exchange membrane with strong mechanical properties, high oxidative stability and good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 It is the SEM image of the cross section of PVDF / SPBI (A) obtained in Comparative Example 1 of the present invention and SPVDF / SPBI (B) obtained in Example 1; Figure 2 This is the contact angle test of PVDF / SPBI and SPVDF / SPBI of the present invention. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] Since pure PVDF nanofibers have strong hydrophobicity, when they are used as porous substrates and composited with polyelectrolyte membranes, they have poor compatibility with polyelectrolytes, which leads to the easy appearance of voids and defects in the polyelectrolyte during the filling process, which has a certain influence on the mechanical properties and electrochemical properties of the composite membrane. Therefore, the present invention provides a dual-functionalized SPVDF / SPBI composite proton exchange membrane and a preparation method thereof, wherein a PVDF nanofiber substrate coated with polydopamine (PDA) and diphenyl sulfonate (BDSA) is prepared by a one-step co-deposition coating strategy of dopamine and diphenyl sulfonate (BDSA), and a dual-functionalization treatment of the surface of PVDF nanofibers is achieved, and then the modified PVDF nanofibers are filled with sulfonated polybenzimidazole (SPBI) to prepare a composite proton exchange membrane; at the same time, in the preparation process of the composite proton exchange membrane, a certain amount of 1.4-dibromobutane is added as a cross-linking structural unit, and the cross-linking filling effect between PVDF and SPBI is further improved through chemical reaction. Functionalization with polydopamine (PDA) and disulfonic acid benzidine can not only greatly improve the hydrophobicity of PVDF nanofibers and strengthen the interaction between PVDF nanofibers and SPBI polymers, but also introduce a large number of amino and sulfonic acid groups, which can not only directly increase the proton transfer rate, but also form ionic acid-base pairs by interacting with the functional groups on the SPBI main chain, thereby constructing an effective hydrophilic channel to promote proton transfer and improve conductivity.

[0012] In a first aspect, the present invention provides a method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane, comprising the following steps: (1) Preparation of bifunctionalized PVDF (SPVDF): PVDF nanofibers were immersed in a buffer solution containing dopamine, and then diphenylamine sulfonate was added to perform a one-step co-precipitation reaction. After post-treatment, bifunctionalized PVDF was obtained, which was recorded as SPVDF. (2) The bifunctionalized PVDF is immersed in a sulfonated polybenzimidazole solution, and a cross-linking agent is added, and then dried to obtain a bifunctionalized SPVDF / SPBI composite proton exchange membrane.

[0013] Preferably, in step (1), in the buffer containing dopamine, the dopamine concentration is 2.0-3.0 g / L, the buffer concentration is 0.15-3.4 g / L; and the buffer is Tris.

[0014] Preferably, in step (1), the mass ratio of dopamine to diphenylamine sulfonate is (0.3-0.6): (0.15-0.3).

[0015] Preferably, in step (1), the one-step co-deposition reaction is carried out under stirring conditions at 20-45°C for 12-24 hours; the post-treatment specifically comprises: taking out the PVDF nanofibers after the one-step co-deposition reaction, washing and drying them to obtain bifunctional PVDF.

[0016] Preferably, in step (2), the sulfonated polybenzimidazole solution is obtained by dissolving sulfonated polybenzimidazole in dimethyl sulfoxide at 60-80°C.

[0017] Preferably, in step (2), the preparation step of sulfonated polybenzimidazole comprises: dissolving polybenzimidazole powder in dimethyl sulfoxide, adding sodium hydride under nitrogen protection to carry out the first step reaction; wherein the mass ratio of polybenzimidazole to sodium hydride is 1:(0.5-0.8); After the first step reaction is completed, 1,3-propane sultone is added to carry out the second step reaction; wherein the mass ratio of 1,3-propane sultone to polybenzimidazole is (0.5-0.8):1; After the second step reaction is completed, the clarified reaction solution is poured into excess acetone to precipitate, and the precipitate is washed with a Na2CO3 solution and deionized water, centrifuged and dried to obtain sulfonated polybenzimidazole.

[0018] Further preferably, the polybenzimidazole powder is dissolved in dimethyl sulfoxide at 75-85°C; the ratio of the polybenzimidazole powder to dimethyl sulfoxide is 1 g: (30-50) mL; the first step reaction is carried out at 35-45°C for 2.5-3.5 h; and the second step reaction is carried out at 35-45°C for 12-18 h.

[0019] Preferably, in step (2), the concentration of the sulfonated polybenzimidazole solution is 30 to 50 g / L.

[0020] Preferably, in step (2), the crosslinking agent includes 1.4-dibromobutane; the ratio of sulfonated polybenzimidazole to 1.4-dibromobutane is (0.8-1.0) g: (1.0-2.0) mL; the sulfonated polybenzimidazole is relative to each 0.01 m 2 The amount of bifunctional PVDF used is 0.8-1.0 g, wherein too little cross-linking agent will result in insufficient cross-linking.

[0021] Preferably, in step (2), drying is first carried out at 40-60°C for 48-36 hours, and then at 60-80°C for 12-24 hours.

[0022] In a second aspect, the present invention provides a bifunctional SPVDF / SPBI composite proton exchange membrane prepared by the above preparation method.

[0023] The present invention performs surface functionalization treatment on a PVDF nanofiber substrate by a one-step co-deposition method, then adds 1.4-dibromobutane as a cross-linking reaction structural unit, and further improves the filling effect of the SPBI polyelectrolyte through a chemical cross-linking reaction between 1.4-dibromobutane and functionalized PVDF and SPBI on the basis of electrostatic interaction between functional groups, thereby solving the problems of unsatisfactory compatibility between the PVDF substrate and the organic polyelectrolyte and low conductivity, and providing a new modification idea for the application of the PVDF substrate in the field of proton exchange membranes.

[0024] The present invention is further described in detail below through specific examples and comparative examples, wherein the PVDF nanofiber substrate is PVDF electrospun nanofiber, length × width = 10 cm × 10 cm; sulfonated polybenzimidazole (SPBI) is prepared by the following method: At 80 °C, 1 g of polybenzimidazole (analytical grade, purchased from Shengjun Plastic Technology Co., Ltd.) powder was dissolved in 40 mL of dimethyl sulfoxide. Then, 0.64 g of sodium hydride was added under the protection of nitrogen and reacted at 40 °C for 3 h. After the reaction was completed, 0.64 g of 1,3-propanesultone was added and reacted at 40 °C for 15 h. After the reaction was completed, the clarified mixed solution was poured into excess acetone to precipitate, and the precipitate was collected by filtration. The precipitate was then washed with 1M Na2CO3, and then washed with deionized water until neutral. The precipitate was collected by centrifugation and dried at 80 °C for 12 h to obtain sulfonated polybenzimidazole (SPBI), and its sulfonation degree was 190% as tested by nuclear magnetic hydrogen spectrum.

[0025] Example 1 A method for preparing a dual-functional SPVDF / SPBI composite proton exchange membrane comprises the following steps: (1) Preparation of bifunctional PVDF (SPVDF): The PVDF nanofiber substrate was immersed in 150 mL of 2 g / L dopamine solution, 0.035 g of Tris buffer was added, and air was continuously introduced into the mixed solution using an air compressor. Subsequently, 0.15 g of diphenyl sulfonate (BDSA) was added and reacted at 40 °C for 24 h. After the reaction, the PVDF nanofibers were removed, washed with deionized water, and dried at 50 °C to obtain a bifunctional PVDF substrate (SPVDF).

[0026] (2) Preparation of SPVDF / SPBI composite membrane: Take 0.8 g of the prepared SPBI solid, dissolve it in 20 mL of dimethyl sulfoxide at 80 °C and pour it into a glass tank (i.e., the concentration of the sulfonated polybenzimidazole solution is 40 g / L). Place the glass tank on a flat hot plate, then immerse the SPVDF fiber substrate in it, add 2.0 mL of 1.4-dibromobutane, dry at 40 °C for 48 h, then heat to 80 °C and dry for 12 h to obtain an SPVDF / SPBI composite proton exchange membrane.

[0027] Comparative Example 1 A method for preparing a composite proton exchange membrane, which differs from Example 1 in that SPBI and pure PVDF fiber are directly composited, specifically comprising the following steps: Take 0.8 g of the prepared SPBI solid, dissolve it in 20 mL of dimethyl sulfoxide at 80 °C and pour it into a glass tank. Place the glass tank on a flat hot stage, then immerse the pure PVDF fiber substrate in it. After drying at 40 °C for 48 h, heat it to 80 °C and dry it for 12 h to obtain a PVDF / SPBI composite proton exchange membrane.

[0028] Comparative Example 2 A method for preparing a composite proton exchange membrane, which differs from Example 1 in that 1,4-dibromobutane is removed, and other steps and conditions are the same as those in Example 1, specifically comprising the following steps: Take 0.8 g of the prepared SPBI solid, dissolve it in 20 mL of dimethyl sulfoxide at 80 °C and pour it into a glass tank. Place the glass tank on a flat hot plate, and then immerse the SPVDF fiber substrate in it. After drying at 40 °C for 48 h, heat it to 80 °C and dry it for 12 h to obtain a composite proton exchange membrane.

[0029] Comparative Example 3 A method for preparing a pure SPBI proton exchange membrane specifically comprises the following steps: 0.8 g of the prepared SPBI (sulfonation degree 190%) solid was dissolved in 20 mL of dimethyl sulfoxide at 80 °C and poured into a glass tank (i.e., the concentration of the sulfonated polybenzimidazole solution was 40 g / L). The glass tank was placed on a flat hot plate, dried at 40 °C for 48 h, and then heated to 80 °C and dried for 12 h to obtain a pure SPBI proton exchange membrane.

[0030] Structural characterization and performance testing The test conditions are described as follows: (1) SEM morphology: The cross-sectional morphology was observed using a scanning electron microscope (SEM). The interface was obtained by brittle fracture of the membrane test sample in liquid nitrogen.

[0031] (2) Contact angle test: The water contact angle test was carried out at room temperature on a contact angle measurement system (JC2000C, POWEREACH), and the contact angle change of the water droplet on the test sample interface over time was recorded.

[0032] (3) Tensile strength and elongation at break: The film was cut into rectangular strips with a length × width = 40 mm × 20 mm and tested under a relative humidity of 100%. The tensile speed during the test was 20 mm / min.

[0033] (4) Ion exchange capacity test: The ion exchange capacity (IEC) was determined by titration. The membrane was immersed in deionized water for 24 h to allow it to fully absorb water, then immersed in NaCl (1 M) solution for 24 h, and then titrated with NaOH (0.01 M) solution. Phenolphthalein solution was used as an indicator during the titration process. The IEC value was calculated as follows: IEC=(C NaOH ×V NaOH ) / m dry Among them C NaOH and V NaOH are the concentration and volume of NaOH solution, m dry The quality of the dry film.

[0034] (5) Oxidative stability: The test film sample was placed in an oven at 80 °C for 24 h and then weighed and recorded as mass m1. It was then immersed in Fenton solution (H2O2 30 wt%, Fe 2+ 3ppm). After a certain period of time, take out the test film sample (6h, 12h), wash it with deionized water and dry it in an oven at 80℃ for 24h, and record the mass as m2. According to the mass of the film before and after treatment, calculate the residual mass (RW): RW (wt%) = (m2 / m1)×100 (6) Proton conductivity: The resistance of the membrane was tested using the AC impedance method on a frequency response analyzer with a frequency scanning range of 1-10 7 Hz, the AC signal amplitude is 100mV. The cut membrane (1.5cm×2.5cm) was tested by two-electrode AC impedance method. Before the test, the membrane sample was placed in deionized water at room temperature to reach saturation. The proton conductivity σ (S / cm) of the membrane was calculated by the following formula:

[0035] Wherein, L and A are the distance between the two electrodes and the effective cross-sectional area of ​​the membrane to be tested between the two electrodes, respectively, and R is the resistance of the membrane, which is calculated from the data obtained from the AC impedance test.

[0036] The performance of the films obtained in each embodiment and comparative example was tested under the above test conditions. The results are as follows Figure 1-Figure 2 And as shown in Table 1.

[0037] The cross-sectional SEM scanning of Example 1 and Comparative Example 1 showed the following results: Figure 1 As shown in Figure A, it can be seen that the PVDF / SPBI membrane of Comparative Example 1 has a poor filling effect and has many cavities and defects in the structure, which is mainly due to the poor compatibility between pure PVDF fiber and SPBI. Figure 1 Middle (B) shows a better filling effect. The PVDF fiber is completely filled with SPBI, showing a relatively compact structure, which is mainly due to the effective electrostatic interaction and chemical cross-linking between the modified PVDF surface and the SPBI structure. The contact angle test was performed on Example 1 and Comparative Example 1. The results are as follows Figure 2 As shown, it can be seen that Example 1 exhibits better hydrophilicity, with a contact angle with water of only 31° (1 second), while the contact angle with water of Comparative Example 1 is 47° (1 second), and as time goes on, water droplets can quickly spread on the SPBI / SPVDF composite proton exchange membrane of Example 1.

[0038] Table 1 Performance comparison of the composite proton exchange membranes obtained in each embodiment and comparative example

[0039] As shown in Table 1, Example 1 and Comparative Examples 1-3 were tested for tensile strength. By comparison, it can be seen that Example 1 shows better strength and toughness, and its elongation at break is as high as 210%, which is mainly attributed to the strong mechanical support of PVDF and the electrostatic and chemical crosslinking between SPVDF and SPBI. At the same time, Example 1 also shows better oxidation stability than Comparative Examples 1-3. After immersion for 12 hours, its residual mass is still 90%, showing higher oxidation stability; while the oxidation stability of the pure SPBI proton exchange membrane obtained in Comparative Example 3 is relatively the worst.

[0040] Example 1 and Comparative Examples 1-3 were also tested for ion exchange capacity (IEC) and proton conductivity. By comparing the results in Table 1, it can be seen that the IEC value of Example 1 is significantly higher than that of Comparative Example 1, and its highest proton conductivity reaches 47mS cm at 80°C. -1, which is also significantly better than comparative examples 2-3. This is mainly due to the fact that the grafting of disulfonic acid benzidine introduces a large number of sulfonic acid groups, which provides a wide range of migration sites for the transmission of protons. At the same time, -NH2 in its structure and -SO3H in SPBI can also form an ionic acid-base pair to provide a hydrophilic channel for the rapid transmission of protons and promote proton transmission. In addition, the presence of the cross-linking agent effectively improves the cross-linking filling effect between PVDF and SPBI, which shows that the reaction system of the present invention produces a synergistic effect and effectively improves the comprehensive performance of the obtained composite proton exchange membrane.

[0041] In summary, the present invention provides a dual-functionalized SPVDF / SPBI composite proton exchange membrane and a preparation method thereof, which mainly comprises firstly performing a dual-functionalization treatment on the surface of PVDF nanofibers by a one-step co-deposition coating strategy with polydopamine (PDA) and diphenyl sulfonate (BDSA) and a PVDF nanofiber substrate, thereby preparing SPVDF; and then filling the prepared SPBI into the SPVDF substrate to prepare an SPVDF / SPBI composite proton exchange membrane. Tests of tensile strength, oxidation stability, proton conductivity, etc. show that the present invention utilizes a PVDF nanofiber substrate as a mechanical support material, and performs a dual-functionalization treatment on the surface of PVDF nanofibers by a one-step co-deposition coating strategy with polydopamine (PDA) and diphenyl sulfonate (BDSA), while introducing amino and sulfonic acid functional groups on the PVDF surface. Then, the SPVDF substrate is filled with sulfonated polybenzimidazole (SPBI), and a certain amount of 1.4-dibromobutane is added as a cross-linking structural unit. 1.4-dibromobutane reacts with the amino groups of the SPVDF and SPBI structures respectively, and the cross-linking filling effect between PVDF and SPBI is further improved by chemical reaction. The functionalization treatment of polydopamine (PDA) and disulfonic acid benzidine can not only greatly improve the hydrophobicity of PVDF nanofibers, but also strengthen the interaction between PVDF nanofibers and SPBI polymers. At the same time, the introduction of a large number of amino and sulfonic acid groups can not only directly increase the proton transfer rate, but also form ionic acid-base pairs by interacting with the functional groups on the SPBI main chain, thereby constructing an effective hydrophilic channel to promote proton transfer and improve the conductivity. The present invention finally prepares a proton exchange membrane material with strong mechanical properties, high oxidative stability and good conductivity.

[0042] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane, characterized in that: The following steps are involved: (1) The PVDF nanofibers are immersed in a buffer solution containing dopamine, and then diphenylamine sulfonate is added to perform a one-step co-precipitation reaction, and bifunctional PVDF is obtained after post-treatment; (2) The bifunctionalized PVDF is immersed in a sulfonated polybenzimidazole solution, and a cross-linking agent is added, and then dried to obtain a bifunctionalized SPVDF / SPBI composite proton exchange membrane.

2. The method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (1), in the buffer containing dopamine, the dopamine concentration is 2.0-3.0 g / L, and the buffer concentration is 0.15-3.4 g / L; the buffer is Tris.

3. The method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (1), the mass ratio of dopamine to diphenylamine sulfonate is (0.3-0.6): (0.15-0.3).

4. The method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (1), the one-step co-deposition reaction is carried out under stirring conditions at 20-45° C. for 12-24 hours; the post-treatment specifically includes: taking out the PVDF nanofibers after the one-step co-deposition reaction, washing and drying them to obtain bifunctional PVDF.

5. The method for preparing a bifunctional SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (2), the sulfonated polybenzimidazole solution is obtained by dissolving sulfonated polybenzimidazole in dimethyl sulfoxide at 60-80° C.; the concentration of the sulfonated polybenzimidazole solution is 30-50 g / L.

6. The method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (2), the preparation step of sulfonated polybenzimidazole includes: dissolving polybenzimidazole powder in dimethyl sulfoxide, adding sodium hydride under nitrogen protection to carry out the first step reaction; wherein the mass ratio of polybenzimidazole to sodium hydride is 1:(0.5-0.8); After the first step reaction is completed, 1,3-propane sultone is added to carry out the second step reaction; wherein the mass ratio of 1,3-propane sultone to polybenzimidazole is (0.5-0.8):1; After the second step reaction is completed, the clarified reaction solution is poured into excess acetone to precipitate, and the precipitate is washed with a Na2CO3 solution and deionized water, centrifuged and dried to obtain sulfonated polybenzimidazole.

7. The method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane according to claim 6, characterized in that: The polybenzimidazole powder is dissolved in dimethyl sulfoxide at 75-85°C; the ratio of the polybenzimidazole powder to dimethyl sulfoxide is 1g: (30-50)mL; the first step of the reaction is at 35-45°C for 2.5-3.5h; the second step of the reaction is at 35-45°C for 12-18h.

8. The method for preparing a dual-functionalized SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (2), the cross-linking agent includes 1.4-dibromobutane; The ratio of the sulfonated polybenzimidazole to the 1.4-dibromobutane is (0.8-1.0) g: (1.0-2.0) mL; The sulfonated polybenzimidazole is relative to each 0.01m 2 The usage of the bifunctionalized PVDF is 0.8-1.0 g.

9. The method for preparing a bifunctional SPVDF / SPBI composite proton exchange membrane according to claim 1, characterized in that: In step (2), drying is first carried out at 40-60°C for 48-36 hours, and then at 60-80°C for 12-24 hours.

10. A bifunctional SPVDF / SPBI composite proton exchange membrane prepared by the preparation method according to any one of claims 1 to 9.